ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH KOTA BEKASI TAHUN 2010-2014 - Budi Tri Rahardjo, Ak., M.Ak., CA; Juliantika Juliantika (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
The study is done to the effectiveness and the contribution of motor vehicle taxes and import turning the vehicle ownership transfer to the local revenue in Bekasi city. This research was done in SAMSAT the city of Bekasi. Methods used for gathering data, through the data secondary. Data secondary obtained by interview, survey, and observation. Methods of analysis data used is the methods of approach deskriptif kualitatif. The results of the analysis show that the admission tax motor vehicle and bea behind the name of motor vehicle very effective. While contributions to tax motor vehicles of revenue original area very good in the amount of 97.286% and for contribution bea behind the name of the motor vehicle against the revenue the original area was in the amount of 25.50%.